2008
DOI: 10.1021/jp710112q
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Molecularly Mediated Assembly of Gold Nanooctahedra for a Glucose Biosensor

Abstract: This article describes the controllable construction of a layered superstructure of gold nanooctahedra via a molecularly mediated assembly and their electrochemical application as a host matrix toward the oxidation of glucose. The layered superstructures of the Au nanooctahedra were confirmed with atomic force microscopy, X-ray electron spectroscopy, and cyclic voltammograms. The effects of the interface of gold spherical nanoparticles and the different layered interface of gold nanooctahedra on the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…They could also detect the multi-plex surface markers of breast cancer cells by using the antibody-conjugated gold nanorod molecular probes ( 373 ). Huang et al recently reported a molecularly mediated assembling strategy to fabricate a layered superstructure of gold nano-octahedra ( 374 ). They used this assembled structure as the host matrix for a glucose sensor.…”
Section: Applications Of Anisotropic Nanomaterialsmentioning
confidence: 99%
“…They could also detect the multi-plex surface markers of breast cancer cells by using the antibody-conjugated gold nanorod molecular probes ( 373 ). Huang et al recently reported a molecularly mediated assembling strategy to fabricate a layered superstructure of gold nano-octahedra ( 374 ). They used this assembled structure as the host matrix for a glucose sensor.…”
Section: Applications Of Anisotropic Nanomaterialsmentioning
confidence: 99%
“…These results demonstrate that agarose film has little effect on the biochemical activity of GOx after immobilization onto an Au surface. It is worthwhile to note that the noncovalent link of ferrocene to the SWCNT was demonstrated in a previous report [13]. Therefore, this study does not include FTIR spectroscopy of the ferrocene/SWCNT hybrids.…”
Section: Resultsmentioning
confidence: 96%
“…Another improved electrical method of contact for flavoenzymes was reported that used the surface-reconstitution of enzymes on a pyrroloquinoline quinine-flavin adenine dinucleotide (FAD) monolayer [10,11] or on an FAD cofactor unit linked to a redox polymer thin film [12]. In addition, with the help of FeðCNÞ 3À 6 , the nanooctahedra act as a good nanoconnectors that electrically come into contact with the active center of the enzyme and the electrode, resulting in high electron-transfer activity and high biocatalytic efficiency [13].…”
Section: Introductionmentioning
confidence: 99%
“…25 The decoration of metallic NPs on multiwalled carbon nanotubes (MWCNTs) has been shown to enhance the conductivity of electrochemical sensors. Hrapovic et al 26 used both nafion-coated single-walled carbon nanotubes (SWCNTs) and Pt(NPs) for the detection of low concentration of hydrogen peroxide (H 2 O 2 ), which was better compared to SWCNTs or Pt(NPs) alone. Au-functionalized MWCNTs have also been employed as a sensing platform in electrochemical sensing of hydroxylamine, paraoxon, laccase from trametes versicolor extracts, and glycan assay on living cancer cells.…”
Section: Introductionmentioning
confidence: 99%